A Comparative Study of Efficacy of Intrathecal Levobupicaine and Bupivacaine for Caesarean Section - Piyush Kumar Sengar; Sweta Lal (International Journal of Health and Clinical Research, 2021)
Introduction: Spinal Anaesthesia (SA) is the most common anaesthesia technique used for the lower segment Caesarean Section (CS).Due to the various physiological changes affecting the airway, and increased chances of aspiration in pregnancy, administration of General Anaesthesia (GA) to the obstetric patient is a challenging job.Materials and Methods: This prospective randomised, double-blinded study was conducted in the Department of Obstetrics and Gynaecology, Sheikh Bhikari Medical College, HazaribagKolghati Jharkhand. After getting institutional ethics committee approval and written informed consent from all the parturients, a total of 180 parturients who met the inclusion criteria undergoing caesarean section under spinal anaesthesia, were enrolled for study. Results: All the 180 patients who were enrolled in this double-blinded, randomised comparative study, completed the study. There was no dropout and the study results are shown below. Table 1 shows distribution of demographic profile in two study groups. There was no statistically significant difference in age, weight or height distribution among the study groups as ‘p’ value >0.05 and hence the groups were comparable to each other in terms of age, weight and height. Table 2 shows distribution of onset of sensory block, onset of motor block, duration of surgery and duration of analgesia in two study groups. There was statistically significant difference in onset of sensory block and motor block and duration of analgesia and no statistically significant difference in duration of surgery. Conclusion: Thus, in conclusion, levobupivacaine seems to be an effective alternative to intrathecal bupivacaine in infra-umbilical surgeries like caesarean section with reduced toxic potential and excellent quality of analgesia.